Factors Affecting Buying Behavior of Eco-Friendly Products in Nepal - Khatri, Shyam Kaji; Shrestha, Narayan Kumar (Bagiswori Journal, 2025)
The purpose of this study is to investigate the variables influencing Nepalese consumers’ purchasing decisions for eco-friendly goods. Using judgmental sampling, 384 consumers of green products provided the key data. The data analysis was carried out utilizing software such as SPSS and SMART PLS 4. Model fit was attained by the use of confirmatory factor analysis. The parameters were estimated and research hypotheses were tested using structural equation modeling. This study discovered that Nepalese consumers’ purchasing decisions for eco-friendly products were significantly influenced by a number of criteria, including product availability, price, quality, features, and environmental consciousness. The study’s conclusions will assist green marketers in creating creative approaches to draw clients and boost revenue.